Home and Online Management and Evaluation of Blood Pressure (HOME BP) using a digital intervention in poorly controlled hypertension: randomised controlled trial - McManus, R; Little, P; Stuart, B; Ogburn, E; Allen, J (BMJ Publishing Group, 2021)
Objective: The HOME BP trial aimed to test a digital intervention for management of hypertension in primary care combining self-monitoring of blood pressure with guided self-management.